Long-term stability in the gut microbiome over 46 years in the life of Billy Apple®. (December 2017) - Jayasinghe, Thilini N.; Hilton, Craig; Tsai, Peter; Apple, Billy; Shepherd, Peter; Cutfield, Wayne S.; O'Sullivan, Justin M.
Abstract: There is currently a lack of long-term longitudinal studies investigating the stability of the microbiome. In this n-of-one study, we characterised the gut microbial composition of artist Billy Apple® from stool samples collected 45 years apart in 1970 and 2016. We observed that 45% of the microbial species were retained over the 45 year interval. Moreover, components of Apple's microbiome associated with the allele frequency at seven SNPs in his genome. Collectively, our results are consistent with a genetic component contributing to the selection and maintenance of core members within the artist's microbiome over his life-time.